Avaliação da inativação fotodinâmica em bactérias multirresistentes - Caires, Cynthia Suzyelen Albuquerque (2021)
The growing number of antibiotic-resistant bacteria is emerging, which the development of new technology is needed to kill multi-resistant bacteria. The present work aimed to evaluate the photodynamic inactivation (PDI) by using eosin methylene blue (GIEMSA) and sodium copper chlorophyllin (E-141ii) as photosensitizer (PS) agents against Staphylococcus aureus (S. aureus) ATCC 25923 and S. aureus MRSA (Genbank accession number Mh087437), as well as against non-resistant E. coli strain (ATCC 25922) and a mcr-1 positive E. coli strain (CCBH 23593) under light doses in the 30-45 J.cm-2 range provided by a LED device emitting at 625 nm. The PDI experiments were performed using the strains in which five PS concentrations (0.0, 1.0, 2.5, 5.0, 10.0 and 20.0 µM) for S. aureus, and (0.0, 5.0, 10.0, 20.0, 40.0 e 50.0 µM) for E. coli. After PS incubation, the samples were divided in two groups, one kept in the dark and another submitted to illumination. Then, the bacterial inactivation was determined 18 h after the incubation at 37 °C by counting the colony-forming units (CFU). The results demonstrated that GIEMSA is effective against S. aureus ATCC and S. aureus MRSA and also against mcr-1 positive E. coli strain. Similarly to the non-resistant strain, multi-resistant strain was susceptible to the photoinactivation under red light irradiation using GIEMSA as photosensitizer. The GIEMSA promoted 100% of growth inhibition of mcr-1 positive E. coli using a low PS concentration (10 µM) when illumiated at 625 nm with an energy dose of 45 J cm-2, and for S. aureus ATCC and S. aureus MRSA 100% of growth inhibition over 10 µM when irradiated by red light using a dose of 30 J cm−2. The results also showed that E-141ii can be applied as an effective PS for photoinactivation of S. aureus ATCC and S. aureus MRSA. The results revealed that the bacterial growth was completely inhibited at concentrations over 5 µM of PS for S. aureus (MSSA) and over 10 µM of PS for S. aureus (MRSA) when irradiated by red light at 30 J cm−2. The present study also evaluated the PS´s membrane affinity by partition coefficient, which the data demonstrated that both PSs revealed to have membrane affinity. Additionally, the toxicity mechanisms of the IFD process were evaluated by determining the production of reactive oxygen species (ROS) and singlet oxygen (1O2) by the PSs when subjected to light irradiation. It was observed that the GIEMSA produces both type I and type II mechanisms, generating ROS and 1O2, while E-141ii only produces ROS. In summary, the present findins showed that GIEMSA could be successfully applied as a PS for inactivation of colistin-resistant E. coli (mcr-1 positive) and non-multidrug resistant E. coli, S. aureus methicillin resistant and sensitive, while E-141ii has a great pontencial for PDI application against methicillin-resistant and sensitive S. aureus strains.